Robust interferon-a and IL-12 responses by dendritic cells are related to efficient CD4+ T-cell recovery in HIV patients on ART - Tan, D.; Yong, Y.; Lim, A.; Tan, H.; Kamarulzaman, A.; French, M.; Price, Patricia (2011)
Amongst HIV patients with successful virological responses to antiretroviral therapy (ART), poor CD4+ T-cell recovery is associated with low nadir CD4+ T-cell counts and persistent immune activation. These factors might be influenced by dendritic cell (DC) function. Interferon-a-producing plasmacytoid DC and IL-12-producing myeloid DC were quantified by flow cytometry after stimulation with agonists to TLR7/8 (CL075) or TLR9 (CpG-ODN). These were compared between patients who achieved CD4+ T-cell counts above or below 200 cells/µL after 6months on ART (High vs. Low groups). High Group patients had more DC producing interferon-a or IL-12 at Weeks 6 and 12 on ART than Low Group patients. The frequencies of cytokine-producing DC at Week 12 were directly correlated with CD4+ T-cell counts at baseline and at Week 12. Patients with good recovery of CD4+ T-cells had robust TLR-mediated interferon-a responses by plasmacytoid DC and IL-12 responses by myeloid DC during early ART (1-3months). © 2011 Elsevier Inc.